1993
DOI: 10.1101/gr.2.4.328
|View full text |Cite
|
Sign up to set email alerts
|

Generation of cohesive ends on PCR products by UDG-mediated excision of dU, and application for cloning into restriction digest-linearized vectors.

Abstract: We have Investigated the use of dU excision by uracil N-glycosylase (UDG) to create cohesive ends on PCR fragments "mimicking" those generated by restriction enzymes. The feasibility of this approach for directional and nondirectional cloning using cohesive ends mimicking Sacl or Pstl ends is demonstrated by the subcloning of a 383 to 388-bp fragment of bovine basic flbroblast growth factor into restriction enzyme-linearized pTTT318U. UDG-mediated cohesive ends imperfectly matched to Pstl-generated vector ends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…that some particulate air pollutants also trigger an inflammatory response in the lung (13,15). We have demonstrated that NF-B, a common transcriptional activator of several inflammatory genes (26,27), regulates IL-6 transcription in a lung epithelial cell line exposed to ROFA. IL-6 is a multifunctional cytokine activated early in the inflammatory response, chronically elevated in association with several environmentally induced respiratory diseases, and released in vitro by lung epithelial cells after ROFA exposure.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…that some particulate air pollutants also trigger an inflammatory response in the lung (13,15). We have demonstrated that NF-B, a common transcriptional activator of several inflammatory genes (26,27), regulates IL-6 transcription in a lung epithelial cell line exposed to ROFA. IL-6 is a multifunctional cytokine activated early in the inflammatory response, chronically elevated in association with several environmentally induced respiratory diseases, and released in vitro by lung epithelial cells after ROFA exposure.…”
Section: Discussionmentioning
confidence: 97%
“…Transcriptional activation of specific inflammatory genes such as IL-1, IL-6, IL-8, and TNF is mediated by NF-B in various cell types under a wide range of conditions (26,27). In lung epithelial cells, nuclear translocation of NF-B has been stimulated with IL-1, TNF (28, 29), phorbol esters (28,30), and asbestos (31).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Earlier we used single-stranded DNA oligomers of different sizes containing dUMP in varying positions and showed that E.coli UNG excises even those uracil residues located near the ends of the single-stranded DNA (9). Such studies are important not only in considering the details of the mechanism of enzyme action but also in increasing the usefulness of UNG in DNA research (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, uracil excision DNA assembly makes use of oligonucleotides where selected thymines are replaced by uracils. This is a non-mutagenic and PCRtolerated replacement, as the uracil is able to form base pairs with adenine nucleotides on the complementary strand [2][3][4]. Following PCR, the uracils are selectively removed by treatment with uracil DNA glycosidase, leaving a chemically unstable phosphoribose backbone.…”
Section: Introductionmentioning
confidence: 99%